Paulus sebagai Teladan Pendidik Kristen Masa Kini - Sadono, Sentot; Sahartian, Santy (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2020)
Christian educator examples are examples that are carried out or shown by practitioners of Christian education through imitating the quality of Christian life, so that by observing the life of educators students get lessons that affect their understanding and behavior. The importance of the unity of words and deeds lies in the ideal that an educator teaches not only with his words but also with his lifestyle Paul has exemplified, to Christian educators today, the basic principles that an educator should have in teaching. He exemplifies the importance of having broad insight as a basis and starting point for teaching, developing one's potential to have a desire to continue learning, teaching skills as a practical implementation; and, he exemplifies visionism as a strategic thought and effort that is preventive and anticipatory in facing the future. Abstrak: Teladanan pendidik Kristen adalah keteladanan yang dilakukan atau ditunjukkan oleh para pelaku pendidikan Kristen melalui peneladanan kualitas kehidupan Kristiani, sehingga dengan mengamati kehidupan pendidik peserta didik beroleh pelajaran yang memengaruhi pemahaman dan perilaku hidupnya. Pentingnya kesatuan kata dan perbuatan terletak dalam idealitas bahwa seorang pendidik mengajar bukan hanya dengan tutur katanya melainkan juga dengan model hidupnya Paulus telah meneladankan, kepada pendidik Kristen masa kini yaitu asas- asas pokok yang perlu dimiliki seorang pendidik dalam mengajar. Ia meneladankan pentingnya kepemilikan wawasan yang luas sebagai dasar dan titik tolak pengajaran, mengembangkan potensi diri mempunyai keinginan untuk terus belajar, kecakapan mengajar sebagai implementasi praktisnya; dan, ia meneladankan kevisioneran sebagai pemikiran dan usaha strategis yang bersifat preventif dan antisipatif menghadapi masa-masa mendatang.